THEORETICAL ANALYSIS OF TEENAGERS’ COMMUNICATIVE SPHERE COMPONENTS - Павленко, Т. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The the article considers the teenagers basic personal qualities which influence the development of the communicative sphere at this age, analyzes the main approaches to determining the components of the teenager’s communicative sphere, proposes the author’s own structure and analyzes it